The Soybean Rfg1 Gene Restricts Nodulation by Sinorhizobium fredii USDA193 - Fan, Yinglun; Liu, Jinge; Lyu, Shanhua; Wang, Qi; Yang, Shengming; Zhu, Hongyan (Frontiers in Plant Science, 2017)
Sinorhizobium fredii is a fast-growing rhizobial species that can establish a nitrogen-fixing symbiosis with a wide range of legume species including soybeans (Glycine max). In soybeans, this interaction shows a high level of specificity such that particular S. fredii strains nodulate only a limited set of plant genotypes. Here we report the identification of a dominant gene in soybeans that restricts nodulation with S. fredii USDA193. Genetic mapping in an F2 population revealed co-segregation of the underlying locus with the previously cloned Rfg1 gene. The Rfg1 allele encodes a member of the Toll-interleukin receptor/nucleotide-binding site/leucine-rich repeat (TIR-NBS-LRR) class of plant resistance proteins that restricts nodulation by S. fredii strains USDA257 and USDA205, and an allelic variant of this gene also restricts nodulation by Bradyrhizobium japonicum USDA122. By means of complementation tests and CRISPR/Cas9-mediated gene knockouts, we demonstrate that the Rfg1 allele also is responsible for resistance to nodulation by S. fredii USDA193. Therefore, the Rfg1 allele likely provides broad-spectrum resistance to nodulation by many S. fredii and B. japonicum strains in soybeans.